2016
DOI: 10.1002/fld.4290
|View full text |Cite
|
Sign up to set email alerts
|

Model reduction and inverse problems and data assimilation with geophysical applications. A special issue in honor of I. Michael Navon's 75th birthday

Abstract: EDITORIALModel reduction and inverse problems and data assimilation with geophysical applications. A special issue in honor of I. Michael Navon's 75th birthdayProfessor Ionel Michael Navon retired in September 2014 from the Scientific Computing Department, Florida State University, Tallahassee, Florida, after a brilliant academic career. Since 1997, he is a fellow of the American Meteorological Society, and recently, he became an honorary member of the Academy of Romanian Scientists. His distinguished pioneeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…The surrogate modeling of high-dimensional vector-valued functions is mainly performed with a reduced-order approach, called reduced-order modeling (ROM). Originally developed for the study of coherent structures in the turbulent boundary layer [1], ROM methods have shown various applications such as aeroelasticity [2], optimal flow control [3], turbulent flows [4,5] or geophysics [6]. Most ROM methods are applied to CFD problems by approximating the high fidelity model as a linear combination of low-dimensional basis vectors, weighted by purposely-tuned parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The surrogate modeling of high-dimensional vector-valued functions is mainly performed with a reduced-order approach, called reduced-order modeling (ROM). Originally developed for the study of coherent structures in the turbulent boundary layer [1], ROM methods have shown various applications such as aeroelasticity [2], optimal flow control [3], turbulent flows [4,5] or geophysics [6]. Most ROM methods are applied to CFD problems by approximating the high fidelity model as a linear combination of low-dimensional basis vectors, weighted by purposely-tuned parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the reduced‐order models (ROMs) technology plays an important role as they are able to simulate physical systems accurately with several orders of magnitude CPU speed‐up. The ROMs have been applied successfully to a number of research fields such as data assimilation, 3 ocean modeling, 4 shallow water equations, 5,6 air pollution prediction, 7 polynomial systems, 8 viscous and inviscid flows, 9 fluid‐structure interaction, 10 aerodynamic shape optimization, 11 large‐scale time‐dependent systems, 12 optimal control, 13 circuit systems, 14,15 inverse problems, 16 fluids, 17 reservoir history matching, 18 and turbulent flows 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Before we continue, we point out that different model reduction techniques have been employed in a wide variety of inverse problems; see, e.g., [12,14,17,19,22,27,[38][39][40][41]47] and the references therein. However, as we explain below, interpolatory model reduction methods [2,3,7] are perfectly suited for the DOT problem and have proven very effective in this setting [20,42].…”
Section: Introductionmentioning
confidence: 99%